Videography – studying ethical uncertainty in alternative entrepreneurship. Issue 4 (19th November 2020) - Skoglund, Annika; Redmalm, David; Berglund, Karin
Abstract : Purpose: The purpose of this paper is to develop videographic methods for the study of alternative entrepreneurship, with a theoretical focus on "ethical uncertainties", exemplified in this paper by the exploration of evolving actions and unpredictable outcomes in a specific case, the Hungarian company Prezi. Design/methodology/approach: By first situating Prezi's alternative entrepreneurship in the turbulent Hungarian political context and situation for the Roma population, this study presents how the methodological foundations of organizational videography have affirmed aesthetic immersion, which is of particular use for the study of ethical uncertainty. Findings: Following a methodological exploration of the specific research design and ethnographic reflections on three ways in which ethical uncertainties arise, this study discusses the videographic possibilities to study something as elusive as ethical uncertainty and its link to alternative futures. Originality/value: The political context in Hungary poses many challenges for organizations that attempt to "do good" and create alternative futures. This paper explains how this political context permeates Prezi's entrepreneurship and research thereof, by highlighting "ethical uncertainty". The combined contribution (paper and videography) invites the reader to think differently about the authority of research, become a viewer and reflect on their own experiences of ethical uncertainty in alternative entrepreneurship.